2015
DOI: 10.1111/1756-185x.12699
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reporting of interventional animal studies in rheumatology: a systematic review using the ARRIVE guidelines

Abstract: Aim: To systematically investigate the quality of reporting of published interventional animal studies in experimental rheumatology.Methods: Original scientific publications in Annals of the Rheumatic Diseases (ARD) and Arthritis and Rheumatism (A&R) from January to December 2012 were identified. Studies were included if they used animal experimental model(s) and involved a treatment intervention. Data were extracted regarding disease type, animal model, intervention type and funding. Each study was assessed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 20 publications
5
33
2
Order By: Relevance
“…While reporting of relevant parameters such as blinding and randomisation was higher in our ‘preclinical’ subsample than what has been reported in other systematic reviews,16 31 76 78–81 the results for the overall sample were generally comparable. Also, and similarly to what was found in these systematic reviews, justification for sample size was rarely reported.…”
Section: Discussioncontrasting
confidence: 41%
“…While reporting of relevant parameters such as blinding and randomisation was higher in our ‘preclinical’ subsample than what has been reported in other systematic reviews,16 31 76 78–81 the results for the overall sample were generally comparable. Also, and similarly to what was found in these systematic reviews, justification for sample size was rarely reported.…”
Section: Discussioncontrasting
confidence: 41%
“…Many systematic reviews and meta-analyses are hindered by inadequate reporting in the primary studies, despite publication and wide adoption and endorsement by many journals of the ARRIVE reporting guidelines e Animals in Research: Reporting In Vivo Experiments 46e48 . In our particular field, a recent study revealed that experimental animal studies published in two of the top journals in rheumatology 2 years after ARRIVE guideline introduction were still deficient, with papers still failing to report on ethics (22%), randomisation (83%), attrition rate (80%), and important adverse events (90%) 49 . In both this meta-analysis and one on animal studies of arthritis pain 42 , not a single primary study reported power calculations or allocation concealment.…”
Section: Reducing Bias and Increasing Quality-of-evidence In Animal Smentioning
confidence: 99%
“…These issues have been well covered by the ARRIVE guidelines 46,47 , however it is worth re-emphasising how important appropriate reporting is to the GRADE evaluation of quality-of-evidence, and thus the ultimate utility of the research e omission of reporting is as detrimental as actually not doing something that impacts research RoB. The most common reporting omissions in preclinical OA-related research are details of ethics, power calculation, randomisation and allocation concealment (blinding), attrition rate, and important adverse events 42,49 .…”
Section: Considering An Animal Study In Oa To Define Quality-ofevidenmentioning
confidence: 99%
“…indeed, our institutional committee (sNUBh iA-CUC) reviewed and approved our study protocol before study commencement. 4 the manner in which experiments are reported-the extent of details in the methods section and the presentation of key results-is a cornerstone of the peer review process and forms the basis for their utility and validity for future research. the dogs were killed at the end of each experiment by intravenous injection of KCl and intramuscular injection of a Zoletil-rompun mixture (4.4 and 2.2 mg/kg) under general anesthesia.…”
Section: The Authors Replymentioning
confidence: 99%